Cytokine Secretion and Pyroptosis of Thyroid Follicular Cells Mediated by Enhanced NLRP3, NLRP1, NLRC4, and AIM2 Inflammasomes Are Associated With Autoimmune Thyroiditis - Guo, Qingling; Wu, Ying; Hou, Yuanyuan; Liu, Yongping; Liu, Tingting; Zhang, Hao; Fan, Chenling; Guan, Haixia; Li, Yushu; Shan, Zhongyan; Teng, Weiping (Frontiers in Immunology, 2018)
Background: Inflammasomes, which mediate maturation of interleukin-1β (IL-β) and interleukin-18 (IL-18) and lead to pyroptosis, have been linked to various autoimmune disorders. This study investigated whether they are involved in the pathogenesis of autoimmune thyroiditis (AIT). Methods: We collected thyroid tissues from 50 patients with AIT and 50 sex- and age-matched controls. Serum levels of free T3, free T4, thyrotropin, thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb) were measured by electrochemiluminescent immunoassays. Expression of several inflammasome components, the NLR family pyrin domain containing 1 (NLRP1), NLRP3, CARD-domain containing 4 (NLRC4), absent in melanoma 2 (AIM2), the apoptosis-associated speck-like protein that contains a caspase recruitment domain (ASC), caspase-1(CASP1), IL-1β and IL-18 was determined by real-time PCR and western blot. Immunohistochemistry was used to localize the expression of NLRP1, NLRP3, NLRC4 and AIM2. The Nthy-ori 3-1 thyroid cell line was stimulated with tumor necrosis factor-α (TNFα), interferon-γ (IFN-γ), interleukin-17A, interleukin-6 and poly(dA:dT). The levels of IL-18 and IL-1β in the cell supernatant were measured by enzyme-linked immunosorbent assay, and lactate dehydrogenase was quantified by absorptiometry. ASC specks were examined by confocal immunofluorescence microscopic analysis. Cell death was examined by flow cytometry, and the N-terminal domain of gasdermin D was detected by western blot analysis. Results: Expression of NLRP1, NLRP3, NLRC4, AIM2, ASC, CASP1, IL-18, IL-1β mRNA and protein was significantly increased in thyroid tissues from patients with AIT, and enhanced posttranslational maturation of CASP1, IL-18 and IL-1β was also observed. Expression of NLRP1, NLRP3, NLRC4 and AIM2 was localized mainly in thyroid follicular cells adjacent to areas of lymphatic infiltration. The thyroid mRNA level of NLRP1 and ASC was correlated to the serum TPOAb and TgAb levels in the AIT group. TNFα and IFN-γ had a priming effect on the expression of multiple inflammasome components in thyroid cells. IFN-γ was found to strengthen poly(dA:dT)-induced cell pyroptosis and bioactive IL-18 release. Conclusions: Our work has demonstrated for the first time that multiple inflammasomes are associated with AIT pathogenesis. The identified NLRP3, NLRP1, NLRC4, AIM2 inflammasomes and their downstream cytokines may represent potential therapeutic targets and biomarkers of AIT.